Astronomical forcing of sedimentary cycles of Late Eocene Liushagang Formation in the Bailian Sag, Fushan Depression, Beibuwan Basin, South China Sea - Cao, Hai-yang; Jin, Si-ding; Sun, Ming; Wang, Hua (Journal of Central South University, 2016)
Sediments in the Liushagang Formation of Late Eocene form a group of key hydrocarbon play fairways in the Beibuwan Basin, South China Sea. As an important reservoir-forming combination, the Liushagang Formation consists of deltaic siliciclastic and show clear sedimentary cyclicity. According to paleontology research and stratigraphic correlation, the boundary between Liushagang Formation (Els) and Weizhou Formation (Ewz) is regarded as the Eocene-Oligocene boundary. The oxygen isotope dating for well cores from the top of the first Member of Liushagang Formation (Els1) and the bottom of the third Member of Weizhou Formation (Ewz3) give an isochron age of 35.2 Ma. Here, we use GR logging data as a paleoenvironmental proxy to conduct a detailed cyclostratigraphic study of the Els1 in the Bailian Sag, Fushan Depression. Power spectra, evolutionary fast Fourier transformation and wavelet analysis all reveal significant sedimentary cycles in Els1. The ratios of cycle wavelengths in these stratigraphic units are 21:5:2.8:1.2:1, and are interpreted as Milankovitch cycles of 400 ka and 96 ka eccentricity, 52 ka obliquity, 22 ka and 19 ka precession cycles, respectively. An astronomical time scale is established by tuning filtered 96 ka eccentricity cycles to a target curve of Well L2 in the Bailian Sag. Based on regional stratigraphic framework, combined with seismic, cores and logging data, the HST of the first member of the Liushagang Formation (Els1) delta in Well L2 was divided into six parasequence sets named Ps1-Ps6. According to the spectrum analysis by Simple Lomb periodogram from PAST program packages, the sediment accumulation rate of each parasequence sets first increased and then decreased as time went by. The sediment accumulation rate of Ps4 reached the maximum (0.127 m/ka) during the most prosperous period of delta prograding. Finally, the duration of each period of parasequence sets and more accurate geological age were calculated on the basis of sediment accumulation rate. The ages of each depth are precisely estimated and provide new constraints on the Late Eocene.